2008
DOI: 10.4278/ajhp.22.5.329
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Television Viewing with Snacking Behavior and Body Weight of Young Adults

Abstract: Associations were found among TV viewing, energy-dense snack consumption, and snacking behavior, and between TV viewing and body weight status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
84
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 48 publications
(54 reference statements)
8
84
0
3
Order By: Relevance
“…Several cross-sectional studies have found an association between TV viewing and paediatric overweight or obesity (1)(2)(3)(4)(5) , some studies have found no significant association (6,7) while others have found a weak positive association (8) or mixed results (9,10) . Several prospective studies have reported that there is a link between the amount of time TV is watched and overweight/obesity through different stages of the life course from early childhood to young adulthood (11)(12)(13)(14)(15)(16)(17) .…”
mentioning
confidence: 99%
“…Several cross-sectional studies have found an association between TV viewing and paediatric overweight or obesity (1)(2)(3)(4)(5) , some studies have found no significant association (6,7) while others have found a weak positive association (8) or mixed results (9,10) . Several prospective studies have reported that there is a link between the amount of time TV is watched and overweight/obesity through different stages of the life course from early childhood to young adulthood (11)(12)(13)(14)(15)(16)(17) .…”
mentioning
confidence: 99%
“…However, very few studies have addressed whether the effect of eating meals during television viewing is over and above that of the overall time spent television watching. The two studies on whether the effect of eating meals during television viewing on body weights is over and above the effect of overall time spent television watching came to seemingly contradictory conclusions (19,20) . A better understanding of the independent importance of television watching and eating while watching television is essential to directing new public programmes to promote healthy eating and to prevent obesity.…”
mentioning
confidence: 99%
“…Observational studies and randomized controlled trials have shown that such advertisements increase children's preference for the advertised foods (16,17) . Television viewing also provides the opportunity to snack (18)(19)(20) , which may increase energy intake (21) . In addition, eating meals in front of the television instead of with the family in a structured setting diminishes the nutritional and psychosocial benefits of family meals (22)(23)(24) .…”
mentioning
confidence: 99%
“…It is likely that parents and siblings may act as role models to encourage children to consume novel food and beverages (20,22,23) . A parent can control his/her child's sweetened beverage consumption by placing restrictions on the number of soft drinks permitted each day (25,26) , limiting the accessibility of regular soft drinks in the home and limiting participation in sedentary behaviours such as viewing television (27) . Evidence also suggests that imposing stringent parental controls can lead to preferences for energy-dense foods and drinks, such as sweetened beverages (20,21,23) .…”
mentioning
confidence: 99%